Fronteiras religiosas híbridas : o entre-lugar da prática do umbandomblé goiano - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
In the present dissertation entitled Hybrid religious borders: the in-between place of the Umbandomblé practice in Goiás, we intend to understand the contributions to the academic production about Afro-Brazilian religions in Goiás and on a national level, as well as to make explicit the hybridization process by means of the actions of the practitioners in a locus of fusion between Umbanda and Candomblé, which produces what we call an in-between place of the Afro-Brazilian sacred practices. There is a consensus in the literature about Afro-Brazilian religions on the intense difficulty in establishing rigid borders between the Afro-diasporic cults. We direct the methodological path through the post-colonial theory relying on narratives of the representatives/leaders of the temples, scholars and followers of Afro-Brazilian religions. We emphasize the importance of speech in understanding the applicability of the concept of hybridism. It is crucial in this study to know who to ask to and her answers, once these always yield contradictory utterances in favor and against the one to whom the identity is attributed. Given the complexity of the subject it is decisive to understand the negotiation both of differences and of belonging in the Afro-Brazilian religions and in what way the elaboration of knowledge in Umbandomblé is treated in scientific studies. How do they adapt, influence and antagonize each other in the course of the shared experiences? We intend to answer these questions by the end of the present study.
Keywords: Religião - Afro-brasileira - Goiás(Estado); Religião Unbandomblé - Hibridização; Fronteiras religiosas - Umbanda e Candomblé; Religion - Afro-Brazilian - Goiás (State); Unbandomblé Religion - Hybridization; Religious borders - Umbanda and Candomblé; CIENCIAS HUMANAS::TEOLOGIA; CIENCIAS HUMANAS::GEOGRAFIA